Bioreactor Design for Microalgae Cultivation - Hermanto, Mochamad Bagus; HS, Sumardi; Hawa, La Choviya; Fiqtinovri, Siti Masithah (Jurnal Teknologi Pertanian, 2011)
Microalgae not only can be developed as a source of food and medicine, but also used for heavy metal removal and used as an alternative energy for biodiesel production due to its contain of proteins, carbohydrates and vitamins and also oil. The objective of the research is to design a bioreactor by using the principle of a closed recirculation system using transparent materials as a medium of circulation and bioreactor design was tested by using microalgae Nannochloropsis oculata to obtain the biomass growth. Based on the experiments, the design can be well employed. The variable of growth factors for Nannochloropsis oculata namely pH, temperature, light intensity, and salinity of water were in the range of requirements needed for cultivation with a value of 7.2-8.3; 25-27Â°C; 1011-1800 lux, and 3-3.2% respectively. Initial concentration of biomassa was 128x104cells/mL, and gave the highest yield Nannochloropsis oculata of 3.293x104cells/mL at 11th day of culture, but decreased on day 12 to 15 for 655x104cells/mL. This is due to depletion of nutrients in culture media. The highest fat content found in day-to-11 was 17.89%.